2021
DOI: 10.1016/j.smrv.2021.101426
|View full text |Cite
|
Sign up to set email alerts
|

Daily associations between sleep and physical activity: A systematic review and meta-analysis

Abstract: The day-today variations of sleep and physical activity are associated with various health outcomes in adults, and previous studies suggested a bidirectional association between these behaviors. The daily associations between sleep and physical activity have been examined in observational or interventional contexts. The primary goal of the current systematic review and meta-analysis was to summarize existing evidence about daily associations between sleep and physical activity outcomes at inter-and intraindivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 82 publications
5
59
1
Order By: Relevance
“…This means that for some participants, being more active on one day can also be associated with less sleep the following night. To date, mostly non-significant day-to-day associations between physical activity and sleep duration the following night have been reported in previous studies (11/14 studies in a recent systematic review; see Atoui et al, 2021). This relative discrepancy with previous findings Fig.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…This means that for some participants, being more active on one day can also be associated with less sleep the following night. To date, mostly non-significant day-to-day associations between physical activity and sleep duration the following night have been reported in previous studies (11/14 studies in a recent systematic review; see Atoui et al, 2021). This relative discrepancy with previous findings Fig.…”
Section: Discussionmentioning
confidence: 70%
“…A recent systematic review and meta-analysis explored the question of whether physical activity on one day was associated with sleep the following night and to what extent sleep on one night was associated with physical activity the following day (Atoui et al, 2021). This review, which included 33 studies conducted in various populations (but none among participants with weight concerns) did not report any clear pattern of associations between several physical activity and sleep outcomes (Atoui et al, 2021). Similarly, another study conducted among adults with overweight or obesity showed no significant day-to-day associations between the two behaviors (measured with an activity monitor) at the group-level (Liao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent clinical and basic research suggests that sleep disorder is a heterogenic disorder and requires multifaceted evaluation to correctly determine the state of sleep and the effects of therapeutic agents [23][24][25]. We evaluated the sleep status of a preclinical pain model so that it would be close to clinical situations by examining the sleep quantity, sleep duration, sleep depth, and the effect on daytime activity using EEG or wheel rotation.…”
Section: Discussionmentioning
confidence: 99%